Effect of planting material and pre-planting storage method on rhizome sprouting, crop stand, and seed rhizome yield of Turmeric (Curcuma longa L.) at Teppi, Southwestern Ethiopia - Abayneh, Behailu Mekonnen; Chanie, Asrade (International Journal on Food, Agriculture and Natural Resources, 2024)
A two-year study experiment was conducted from January 2021 to December 2022 at the Teppi Agricultural Research Center (TARC) with the aim of identifying suitable planting material and an appropriate pre-planting storage method that can enhance turmeric seed quality and yield under rain-fed conditions. The experiment consisted of three planting materials (mother rhizomes, finger rhizomes, and mixed rhizomes) and five pre-planting storage methods (cemented floor, under tree shade, raised mesh-wired bed, pit with grass cover, and pit with soil cover). These factors were factorially arranged using a randomized complete block design with three replications. The results from the analysis of variance revealed that the seed quality, growth, and seed rhizome yield of turmeric were significantly (p<0.05) influenced by the main effect of both planting material and storage method. However, their interaction effect did not significantly affect these attributes (p>0.05). The highest clean and sprouted seed rhizomes, as well as total sprouts, were recorded in mother seed rhizomes and seed rhizomes stored under tree shade. Conversely, storing mother seed rhizomes on cemented floors resulted in the highest seed weight losses. Finger seed rhizomes stored in soil-covered pits produced the highest percentages of non-sprouted and decayed seed rhizomes. Regarding growth attributes, mother seed rhizomes led to the highest plant stands, plant height, stem girth, leaf growth, and tiller number. Storing seed rhizomes under tree shade performed the best across these growth attributes. Turmeric plants grown from mother seed rhizomes yielded a higher number of mother and finger rhizomes per plant and the highest fresh rhizome yield. Likewise, storing seed rhizomes under tree shade resulted in the highest fresh rhizome yield. In general, utilizing mother seed rhizomes and storing them under tree shade improved turmeric seed quality, growth, and seed rhizome yield. Therefore, farmers in the area are recommended to adopt these practices, but further research is needed to assess their economic feasibility.